2007
DOI: 10.1007/s10509-007-9656-8
|View full text |Cite
|
Sign up to set email alerts
|

Infrared study of the extreme carbon stars based on IRAS, 2MASS and ISO data

Abstract: We collected 55 galactic extreme carbon stars from the published literature in this paper. Observational data from IRAS, 2MASS and ISO were analyzed. The results show that the infrared properties of extreme carbon stars are quite different to those for ordinary visual carbon stars. It is shown from IRAS and 2MASS photometric data that extreme carbon stars have much redder infrared colors not only in the far infrared, but also in the near infrared, hence they have much thicker ciucumstellar envelopes and mass l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…According to the IRAS and 2MASS two-color diagrams, evolutionary types of 13 new carbon stars found in this paper and 8 previously known carbon stars without an evolutionary type are also estimated. It should be emphasized that only 55 ECSs have so far been found in our Galaxy (Chen & Shan 2007), while about 30,000 visible carbon stars are found (Skrutskie et al 2001). Therefore, the important result in this paper is that four sources are discovered as new ECSs, and five previously known carbon stars in the Group U of the IRAS LRS are thought to be ECSs.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…According to the IRAS and 2MASS two-color diagrams, evolutionary types of 13 new carbon stars found in this paper and 8 previously known carbon stars without an evolutionary type are also estimated. It should be emphasized that only 55 ECSs have so far been found in our Galaxy (Chen & Shan 2007), while about 30,000 visible carbon stars are found (Skrutskie et al 2001). Therefore, the important result in this paper is that four sources are discovered as new ECSs, and five previously known carbon stars in the Group U of the IRAS LRS are thought to be ECSs.…”
Section: Resultsmentioning
confidence: 87%
“…Evolutionary stages of ECSs are short; thus, only very few of these stars are known so far (Chen & Shan 2007;Chen et al 2010). In addition, they are in the superwind phase and contribute much to the enrichment of the ISM with their strong mass loss (Speck et al 2005(Speck et al , 2009.…”
Section: Introductionmentioning
confidence: 99%
“…Cohen (1979) suggested that ECSs are among the coolest carbon stars known. Because almost all ECSs known so far were found by using the IRAS Low-Resolution Spectrum (LRS) data (Chen and Shan 2007), Volk et al (1992) summarized the LRS spectral characteristics for ECSs as follows: (1) in the IRAS LRS (7-23 µm) the continuum must be relatively flat compared with visual and infrared carbon stars; (2) no recognizable dust emission feature or only a relatively weak SiC emission feature; (3) a downturn near 8 µm should be seen. Volk et al (2000) also pointed out that ECSs' carbon-rich nature is inferred from their lack of silicate dust features in their LRS spectra and supported by their circumstellar chemistry as determined from molecular line observations: CO and HCN emissions are often strong in these objects as in other carbon stars.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Chengalur et al (1993) indicated the nondetection of 1612 MHz satellite line OH maser using the Arecibo radio telescope. Nyman et al (1998) showed the nondetection of SiO maser emission using the Parkes radio telescope.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we speculated that this star might be a "dual chemistry" star in transition from oxygen-rich to carbon-rich phase (Chen and Shan 2007).…”
Section: Introductionmentioning
confidence: 99%